(untitled) (Research, Society and Development, 2020)
Objective: To highlight and discuss through a bibliographic review the main characteristics of the communication in doctor-patient with hearing impairment relationship, as well as its implications on healthcare. Methodology: Integrative literature review, whose articles were found on SciELO and BVS, between 2015 and 2020. Following inclusion criteria, 8 studies were selected for analysis and all of them (100%) were published in Brazilian journals. Results and discussion: It was concluded that the communication has been explored by Health Science in pursuit of strategies which strengthen the relationships between healthcare workers and the hearing-impaired population attended by them. The significance of the communicative act with hearing-impaired patients is evidenced and parallel to supportive aspects, the necessity of Health Professionals to observe the parameters which are involved in the communicative act that validate the verbal communication during medical appointments. Conclusion: It has been observed that the theme is being explored by health sciences in pursuit of strategies which strengthen the relationships between Health workers and the hearing-impaired population, however it is still scarce in the scientific literature. In the health care scenario, the fragilities of the oralized model of communication persist and the need to support health professionals with knowledge that provides the exercise of non-verbal communicative practices, in order to ensure integrated health care for deaf and hard of hearing.